Discourse-cognition-society: current state and prospects of the socio-cognitive approach to discourse - van Dijk, Teun A. (Letrônica, 2016)
This article presents the current state of the art of the socio-cognitive approach in Discourse Studies. The theory relates structures of discourse with social interaction and social structure through a socio-cognitive interface, with the argument that discourse structures and social structures are of a different nature and cannot be related directly. The cognitive theory consists on the one hand, of a personal dimension of personal mental models (i) of the events talked or written about, and (ii) of the communicative situation itself (context models), and on the other hand of a social dimension consisting of socially shared beliefs, knowledge, attitudes and ideologies – which control the personal mental models, and indirectly all discourse. In this way, we are able to explicitly describe how discourses are involved in the reproduction of social problems such as racism or sexism. Moreover, cognitive analysis also describes and explains many aspects of discourse itself, such as all discourse structures based on knowledge (such as local and global semantic coherence, evidentials, etc.), and ideology (such as the polarization of various discourse structures related to Us (ingroup) and Them (outgroup).